2021
DOI: 10.3390/cancers13225763
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Estrogen Receptor Alpha in Oral Squamous Cell Carcinoma

Abstract: Introduction: Several studies suggest an estrogen receptor alpha (ERα)-mediated influence on the pathogenesis of oral squamous cell carcinoma (OSCC), as described for other malignancies that are not considered to be primarily hormone-dependent. Recently, an association between ERα expression and improved survival in oropharyngeal squamous cell carcinoma (OPSCC) has been found. However, the prognostic relevance of ERα in OSCC has not been proven to date. Therefore, the aim of this study was to evaluate ERα expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…A review published in 2022 by Qin et al described the interaction of estrogen receptors and androgen receptors in HNC. Whereas estrogen receptors beta (ERβ; but not estrogen receptor α [ERα]) are expressed in healthy oral mucosa, the expression of estrogen receptors is altered in OSCC, oropharyngeal squamous cell carcinoma, and precancerous oral lesions . A prognostic role of the expression of ERα in oropharyngeal squamous cell carcinoma and OSCC has been suggested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review published in 2022 by Qin et al described the interaction of estrogen receptors and androgen receptors in HNC. Whereas estrogen receptors beta (ERβ; but not estrogen receptor α [ERα]) are expressed in healthy oral mucosa, the expression of estrogen receptors is altered in OSCC, oropharyngeal squamous cell carcinoma, and precancerous oral lesions . A prognostic role of the expression of ERα in oropharyngeal squamous cell carcinoma and OSCC has been suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas estrogen receptors beta (ERβ; but not estrogen receptor α [ERα]) are expressed in healthy oral mucosa, 20 the expression of estrogen receptors is altered in OSCC, oropharyngeal squamous cell carcinoma, and precancerous oral lesions. [21][22][23][24] A prognostic role of the expression of ERα in oropharyngeal squamous cell carcinoma 21,22 and OSCC 23 has been suggested. Differences in hormone receptor expression and hormone responsiveness may account for differences in the development of HNC at different sublocalizations, as suggested for other malignant neoplasms that are not primarily known as hormone-sensitive cancers.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of sex hormones in the development of cancerous lesions in the oral cavity has previously been discussed. In a cohort of 316 patients, the positive expression of estrogen receptor alpha (ERα) was associated with lower OS and RFS, compared to patients with a negative ERα expression status ( 31 ). Gender-specific analyses demonstrated a highly significant prognostic effect of the ERα status in male patients, in which positive ERα was associated with worse survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Doll et al concluded that patients with positive ER-α expression had significantly lower overall and relapse-free survival (RFS) than those with negative ER-α expression. For the primary tumor and primary tumor/primary lymph node metastasis cohorts with ER-positive primary tumors, ER expression was significantly associated with overall survival (OS) and relapse-free survival in males but not in females [ 10 ]. There was a significant correlation between positivity and tumor localization.…”
Section: Reviewmentioning
confidence: 99%